Вплив організаційних та управлінських методів на фінансово-економічну безпеку підприємства - Кодрул, Р. Е. (ХНУРЕ, 2024)
This work is devoted to the influence of management and organization methods, a systemic approach on ensuring the financial and economic security of the enterprise, including analysis and identification of threats, development of strategies, and implementation of measures to ensure stability and development. It emphasizes the importance of organizational structure and management methods in shaping the financial and economic security of the enterprise. The paper discusses how the management system should be adapted to the external and internal environment, how it can be improved, including through feedback loops for continuous control and support of management effectiveness.
Keywords: фінансово-економічна безпека підприємства; управлінські методи